Icelandic permafrost dynamics since the Last Glacial Maximum – model results and geomorphological implications. (1st April 2020) - Etzelmüller, Bernd; Patton, Henry; Schomacker, Anders; Czekirda, Justyna; Girod, Luc; Hubbard, Alun; Lilleøren, Karianne S.; Westermann, Sebastian
Abstract: Iceland's periglacial realm is one of the most dynamic on the planet, with active geomorphological processes and high weathering rates of young bedrock resulting in high sediment yields and ongoing mass movement. Permafrost is discontinuous in Iceland's highlands and mountains over c. 800 m a.s.l, and sporadic in palsa mires in the central highlands. During the late Pleistocene and Holocene, Iceland's periglacial environment varied considerably in time and space, dominated by glacial fluctuations and periglacial processes. To evaluate the dynamics of permafrost in Iceland since the last deglaciation, we use the output of a coupled climate/ice sheet model to force a transient permafrost model (CryoGRID 2) from the Last Glacial Maximum (LGM) through to the present. We find that permafrost was widespread across the deglaciated areas of western, northern and eastern Iceland after the LGM, and that up to 20% of Iceland's terrestrial area was underlain by permafrost throughout the late Pleistocene. This influenced geomorphological processes and landform generation: the early collapse of the marine-based ice sheet together with the aggradation of permafrost in these zones initiated the formation of abundant and now relict rock glaciers across coastal margins. Permafrost degraded rapidly after the Younger Dryas, with a marked impact on slope stability. Permafrost that formed during the Little Ice Age is again thawing rapidly, and an escalation in slope failure and mass-movement might be currently underway. Our study demonstrates that large regions of Iceland have been underlain by permafrost for millennia, facilitating landform development and influencing the stability of steep slopes. Highlights: Paleo-permafrost was widespread in western, northern and eastern Iceland. Up to 20% of the land area of Iceland was underlain by permafrost during the late Pleistocene. The dominant factor restricting permafrost development switched from glacial extent to climate forcing. Landform development and slope stability in Iceland was strongly influenced by long-term permafrost dynamics.